Evaluation of the safety and efficacy of a Polyzene-F nanocoated coronary stent system: A systematic review and single-arm meta-analysis - Bian, Jifang; Yang, Rongyuan; Wang, Dawei; Yu, Huimin; Liu, Yuan; Liu, Qing (Frontiers in Cardiovascular Medicine, 2023)
Abstract Background Stent for coronary heart disease (CHD) requires long term of anti-platelet therapy because of stent thrombosis. Both of the Cobra and Catania Polyzene-F (PzF) stents were designed to decrease stent thrombosis. Here we reviewed the safety and effectiveness of PzF-nanocoated stent. Methods This systematic review with the title was registered in PROSPERO (No.398781). The inclusion criteria was including studies among patients with PzF-nanocoated coronary stents and reported target vessel failure (TVF) and stent thrombosis (ST) as the outcomes, exclusion criteria was excluding reported patients who could not receive the adjunctive medical therapies or lack of necessary endpoints. Reports of PzF-nanocoated stents were searched in PubMed, Embase and Web of Science and other sources. Because of few reports and lack of comparison groups, the single-arm meta-analysis was conducted in R software (v3.6.2), using a random effect model with generic inverse variance method. After heterogeneity test, assessment of evidence quality was conducted in GRADE software. Funnel plots and Egger’s test was performed to evaluate publication bias, and sensitivity analysis to determine the robustness of overall effects. Results Six studies of 1768 subjects were included. The primary endpoint that pooled TVF rate was 8.9% (95% CI 7.5%-10.2%), which was composed of pooled cardiac death (CD) rate (1.5%, 95% CI 0-3%), myocardial infarction (MI) rate (2.7%, 95%CI 0.4-5.1%), target vessel revascularization (TVR) (4.8%, 95%CI 2.4-7.2%) or target lesion revascularization (TLR) (5.2%, 95%CI 4.2-6.4%), while the secondary endpoint ST was 0.4% (95%CI 0.1-0.9%). The funnel plots of TVF, CD, TVR and TLR did not show serious publication bias, and TVF, TVR, TLR showed moderate quanlity evidence in GRADE assessment. The sensitivity analysis showed that TVF, TLR and ST exhibited well stability (I2 = 26.9%, 16.4% and 35.5%, respectively), while the other endpoints showed moderate instability. Conclusion These data indicated that the PzF-nanocoated coronary stents of Cobra and Catania system demonstrated good safety and efficacy in clinical application. However, the sample size of patients included in the reports was relatively small, and this meta-analysis will be updated if there are more studies published in the future.